1994
DOI: 10.1159/000276678
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Behçet’s Disease with Otologic Symptoms

Abstract: Behçet’s disease is generally known as an autoimmune disease. We report a case of Behçet’s disease who had fluctuating hearing loss, tinnitus and dizziness. A 37-year-old woman had bilateral hearing loss in low audiometric frequencies. Audiological and vestibular examinations revealed an inner ear lesion. The patient had an enlarged negative summation potential in the electrocochleogram and a positive glycerol test, which suggested endolymphatic hydrops. The pathological characteristic of Behçet’s disease is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Sudden hearing loss and fluctuating hearing loss were also reported in Behçet's disease [7,8] . Hearing loss in Behçet's disease can be attributed to vasculitis or inflammatory-autoimmune factors [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Sudden hearing loss and fluctuating hearing loss were also reported in Behçet's disease [7,8] . Hearing loss in Behçet's disease can be attributed to vasculitis or inflammatory-autoimmune factors [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Other authors 1,11 found the involvement of the inner ear as a late complication of Behçet's Syndrome (approximately one decade after the onset of the condition), vasculitis (primary pathological lesion of this disease) was considered the only responsible factor for labyrinth disorder. Detailed otology and vestibular examination revealed cochlea and vestibular apparatus abnormalities, in addition to results indicating that 62% of Behçet's Syndrome patients complain of auditory disorders and 37% of them present vertigo symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Behçet's syndrome is an inflammatory disorder of unknown etiology that affects blood vessels, primarily venules, and is characterized by recurrent oral and genital ulcer lesions, uveitis, aphtous-like skin lesions and acne like eruptions 1,2 . There is no isolated infectious agent.…”
Section: Introductionmentioning
confidence: 99%
“…1 Inner ear dysfunction causes various audiovestibular symptoms such as SNHL, tinnitus and vertigo. The presence of SNHL as a part of or in combination with systemic autimmune diseases such as systemic lupus erythematosus (SLE), 6-8 rheumatoid arthritis (RA), 9-12 Behçet's disease, 13,14 Cogan's syndrome, 15,16 and ulcerative colitis 17,18 has been reported.MRL/lpr mice were found to spontaneously develop SNHL as well as SLE by autoimmune mechanisms. The mice carrying the lymphoproliferation (lpr) mutation have defects in the Fas gene, and a defect in negative selection of self-reactive T cells in the thymus.…”
mentioning
confidence: 99%
“…1 Inner ear dysfunction causes various audiovestibular symptoms such as SNHL, tinnitus and vertigo. The presence of SNHL as a part of or in combination with systemic autimmune diseases such as systemic lupus erythematosus (SLE), [6][7][8] rheumatoid arthritis (RA), [9][10][11][12] Behçet's disease, 13,14 Cogan's syndrome, 15,16 and ulcerative colitis 17,18 has been reported.…”
mentioning
confidence: 99%